External validation and calibration of the HoLISTIC Consortium's advanced-stage Hodgkin lymphoma international prognostic index (A-HIPI) in the Brazilian Hodgkin lymphoma registry - Buccheri, Valeria; Moreira, Frederico Rafael; Biasoli, Irene; Castro, Nelson; Villarim, Carolina Colaço; Traina, Fabiola; Silveira, Talita; Praxedes, Monica Kopschitz; Solza, Cristiana; Perobelli, Leila; Baiocchi, Otavio; Gaiolla, Rafael [UNESP]; et al. (Wiley, 2025)
The Hodgkin lymphoma International Study for Individual Care (HoLISTIC) Consortium's A-HIPI model, developed in 2022 for advanced-stage classical Hodgkin lymphoma (cHL), predicts survival within 5 years amongst newly diagnosed patients. This study validates its performance in the Brazilian Hodgkin lymphoma registry. By 2022, the Brazilian HL registry included 1357 cHL patients, with a median 5-year follow-up. Probabilities for 5-year progression-free survival (PFS) and overall survival (OS) were calculated using A-HIPI-model equations. Discrimination (Harrell C-statistic/Uno C-statistic) and calibration measures assessed external validation and calibration. Lab values beyond the allowed range were excluded, mirroring the initial A-HIPI analysis. A total of 694 advanced-stage cHL patients met the original inclusion criteria (age 18–65 years, Stage IIB-IV). Median age was 31 years; 46.3% were females. Stage distribution was IIB (33.1%), III (27.4%), IV (39.5%). Bulky disease in 32.6%. Five-year PFS and OS were 68.4% and 86.0%, respectively. Harrell C-statistics were 0.60 for PFS and 0.69 for OS, and Uno C-statistics were 0.63 for PFS and 0.72 for OS. Calibration plots demonstrated well-calibrated predictions with calibration slopes of 0.91 and 1.03 for 5-year OS and PFS, respectively. Despite differing patient, clinical characteristics, and socioeconomic factors, the baseline prediction tool performed well in the Brazilian cohort, demonstrating adequate discrimination and calibration. This supports its reliability in diverse settings.
Keywords: A-HIPI; advanced stages; classical Hodgkin lymphoma; prognostic model; validation and calibration